Prevalence of Trichomonas vaginalis in prostitutes in Turkey - Tanyüksel, M; Gün, H; Doganci, L (Central European journal of public health, 1996)
Prostitutes are an important group for the transmission of a number of sexually transmitted diseases (STD) all over the world. Infection with T. vaginalis is one of the most common. In this study, the incidence and diagnostic procedures for Trichomonas vaginalis infection as one of the sexually transmitted diseases (STD's) have been studied. In legal prostitutes in Ankara, Turkey, 64 (25%) of 225 vaginal wet smears were positive for T. vaginalis. There was no significant difference between the detection rates of direct phase-contrast microscopy and culture for the identification of T. vaginalis.
Keywords: Humans; prevalence; Female; dospělí; lidé; zvířata; Turecko; Trichomonas Vaginitis; Vagina; vagina; Adult; ženské pohlaví; trichomonádová vaginitida; Turkey; Prevalence; Animals; Trichomonas vaginalis; Sex Work; prostituce